Expectations and sensitivity of the scalar field dark energy reconstruction from the SNe Ia data - Pavluchenko, Sergey A.; Amendola, Luca; Piloyan, Arpine (Arxiv, 2018)
The current paper is addressing the possibility of the Dark Energy scalar field potential reconstruction from the SNe Ia data and the problems arising during the process. We describe the method and test its limits, stability of the reconstruction with respect to the $Ω_m$ and $H_0$ parameters, as well as several issues connected to the errors propagation, with use of synthetic data. After that, we test the method with real Union2.1 and JLA, as well as recent PANTHEON SNe Ia datasets. It worths mentioning that in our approach we assume no {\it Ans\"atzen} on the dynamical variables (e.g., $H(z)$), which makes our method free of any degeneracies and biases which arise if one assume one or another way to parameterize $H(z)$, or the equation of state, or some other variable. On the other hand, the price we pay for this freedom is immense -- although the scheme demonstrates perfect reconstruction in the case of synthetic data, the reconstruction from the real data seems almost impossible, at least on the current data precision level. The errors of the resulting potential and of the kinetic term are huge; for the Hubble parameter they are smaller but still severalfold larger than those obtained with parameterization. Finally, we test the method with non-SNe $H(z)$ datasets, and the results are also disappointing -- similar to the SNe case, the reconstruction is not possible as the reconstructed kinetic term enters the negative values. This could be treated as a manifestation of the insufficient data precision, or as the overestimation of $(H_0, Ω_m)$ values -- we discuss both possibilities.
Gesehen am 12.11.2020